The Influence of Financial Cost On Finance Variety (Al-Mansour Journal, 2022)
Finance cost is considered as a criterion for investment return average which is acceptable for the available and alternative investment chances. Therefore, the investment which does not generate a gain, equivalent at least finance cost, should be rejected.The cost which should be either paid by the investor or by scarify it for other investment chances which may be more profitable. As a result of a variety in capital market, its components cost and risk, that would affect the investor on selecting the suitable variety for finance process for the required investment proposal